ANALISIS PENGARUH RESHUFFLE KABINET INDONESIA BERSATU II TERHADAP HARGA SAHAM LQ45 DI BURSA EFEK INDONESIA - Trisnawati, Ni Komang Dian; Diantini, Ni Nyoman Ayu (E-Jurnal Manajemen, 2013)
This research aimed to analyze the stock price reaction LQ45 in Indonesia Stock Exchange (BEI) and the difference in average abnormal return in the period before and after the announcement of the events reshuffled Cabinet Indonesia Bersatu II on October 18, 2011. The research period consisted of a 100 days estimation period and the event period 7 days. The method used in this research is the “event study” which observe the market reaction to announcements or information from a publication event. The market reaction reflected the abnormal returns obtained from the difference (positive or negative) about the actual return on the announcement day to expected return. The results showed that there are stock price reaction LQ45 in Indonesia Stock Exchange before and after the announcement of the cabinet reshuffle. At the 5% significance level, there are 4 trading days which earn abnormal returns are on   t -3 , t -2 , t -1 and t +1 , with successive values ??of 0.0074, 0.0093, 0.0127 and 0.0118. But there was no difference in average abnormal return in the period before and after the announcement of the events reshuffled cabinet, seen from the test results were not statistically significant. That is, the market reacts, but the information, the market is not efficient in the semi-strong form.
Keywords: abnormal return, reshuffle, event study